2006
DOI: 10.1111/j.1466-7657.2006.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospice – the ideology and perspectives in Estonia

Abstract: Some ideas of the hospice conception (e.g. pain control and psychosocial support) are used in hospitals and general care centres in Estonia, but there is little respect towards dying people and their needs. The idea of interdisciplinary teamwork is not in use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…These findings from clinical practice suggest that in Thailand, palliative and end‐of‐life care are not well developed, as is also the case in Estonia and Latvia as reported by Robinson (2006). Kiik & Sirotkina (2006) demonstrated that hospice concepts were new in Estonia. Only some ideas relating to hospice concepts were employed in hospitals and residential care homes.…”
Section: Discussionmentioning
confidence: 99%
“…These findings from clinical practice suggest that in Thailand, palliative and end‐of‐life care are not well developed, as is also the case in Estonia and Latvia as reported by Robinson (2006). Kiik & Sirotkina (2006) demonstrated that hospice concepts were new in Estonia. Only some ideas relating to hospice concepts were employed in hospitals and residential care homes.…”
Section: Discussionmentioning
confidence: 99%